PENERAPAN METODE TIKRAR DALAM PEMBELAJARAN MUFRODAT SISWA KELAS VII MTS NEGERI 2 KOTA MAKASSAR - Husnul Khatimah Nasir, Husnul; Abdul Qahar Zainal, Qahar; Nur Farida, Farida; Agussalim Beddu Malla, Agus; Andi Hasriani, Hasriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the development of students' ability to learn mufrodat through the application of the Tikrar method in learning mufrodat for students in grade VII Mts Negeri 2 Makassar City. The tikrar method is a method of repeating learning materials several times so that they can be more absorbed into students' understanding. This study applies the Classroom Action Research (ACR). Each cycle consists of stages of planning, implementation of actions, observation, and reflection. Data collection techniques are carried out through observation, tests, and documentation. The results of the study show that the application of the tikrar method has made progress in students' understanding of mufrodat learning. This is evidenced by the increase in the average score of students from the pre-cycle to 37.02, the first cycle to 72.38, and the second cycle to 84.47. The percentage of learning completeness has also improved, namely in the pre-cycle by 13.88%, cycle I reached 41.66%, and cycle II reached 86.11%. The steps taken to achieve the progress of students' learning outcomes include repeating the material until it is attached to the student's understanding, training students to be able to memorize, mention and write mufrodat and Arabic words/sentences with good and correct rules and adding variations to the tikrar method. Thus, the tikrar method has proven to be quite effective in the learning outcomes of Arabic mufrodat students. Keywords: Tikrar method, Mufrodat learning, Arabic, Classroom Action Research, Student learning outcomes.